Artificial ventilation for neurological disease: retrospective analysis 1972-81. Issue 6382 (18th June 1983) - Douglas, J G; Fergusson, R J; Crompton, G K; Grant, I W
Abstract : During the 10 year period 1972-81, 39 patients with neurological disorders referred to a respiratory unit required artificial ventilation, seven on two occasions. The decision to undertake ventilation was usually made on clinical grounds because of deteriorating respiratory effort, ineffective cough, or inability to swallow. Arterial blood gas studies were of limited value in assessing the need for ventilation. The most frequent complication was bronchopulmonary infection which occurred in almost every patient, Staphylococcus pyogenes, Pseudomonas pyocyanea, and coliforms being the organisms most commonly isolated. In contrast, serious complications of tracheostomy and pulmonary thromboembolism occurred infrequently. There were 10 deaths among the 39 patients ventilated on 46 occasions; six were directly attributable to the neurological disease itself but four resulted from complications of artificial ventilation.